Factors Influencing Community Participation of Youth Affairs Committee Members in Mon State Myanmar - Thaung Htet, Atar (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2021)
This research explains factors (usage of social media, social factors, political & factors) most effect on community participation of youth affairs committee members. This research work was conducted in Myanmar before the Military Coup. The CEC (Chief Executive Committees) members were actively participation in Military coup protest. Moreover, most of the committee members exponent the democratic values to community in this times. The study area was selected Mon State because of the media age of Mon state is 26.7 years. Moreover, there were three major ethnic group – Mon , Kayan and Burma lived in Mon state. This condition shows that youth person settled diverse opinions and thoughts in Mon state. The 131 youth affairs committee members were proportionally selected from each layer of Mon state youth affair committee for collect data. Linear regression and descriptive methods was employed to analyze collected data. It was found that social factors and political & legal factors have positively significant effect on community participation of youth leaders. The policy makers of Mon state should provide the opportunities for youth to engage in community development works.